2014
DOI: 10.2478/pjvs-2014-0055
|View full text |Cite
|
Sign up to set email alerts
|

Trueperella pyogenes infections in swine: clinical course and pathology

Abstract: Trueperella pyogenes is an opportunistic pathogen causing purulent infections in pigs and other animal species. T. pyogenes infections in pigs are local and/or generalized depending on the immune status of the animals, their individual susceptibility and environmental factors. The occurrence of these infections on pig farms causes substantial economic losses in breeding and rearing. In sows from the breeding herd, the disease leads to infertility, embryonic death, abortion, and disorders of the menstrual cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…In swine, T. pyogenes is a common agent of pneumonia, pleuritis, endocarditis, osteoarthritis, polyarthritis, mastitis, reproductive tract infections, and septicaemia [13,29,35,44,98,99,100,101,102]. Abscesses—superficial, muscular, or located in different organs—occur frequently, and may lead to the development of systemic purulent infection and inflammation of lungs, liver, kidneys, muscles, bones, joints, or other tissues [13,46,103]. In many cases, these are infection mixed with different microorganisms, as is observed in T. pyogenes infections in cattle.…”
Section: Pathogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In swine, T. pyogenes is a common agent of pneumonia, pleuritis, endocarditis, osteoarthritis, polyarthritis, mastitis, reproductive tract infections, and septicaemia [13,29,35,44,98,99,100,101,102]. Abscesses—superficial, muscular, or located in different organs—occur frequently, and may lead to the development of systemic purulent infection and inflammation of lungs, liver, kidneys, muscles, bones, joints, or other tissues [13,46,103]. In many cases, these are infection mixed with different microorganisms, as is observed in T. pyogenes infections in cattle.…”
Section: Pathogenicitymentioning
confidence: 99%
“…In many cases, these are infection mixed with different microorganisms, as is observed in T. pyogenes infections in cattle. Diseases of swine associated with T. pyogenes are an emerging clinical, epidemiological, and economic problem, because they usually result in the necessity for the elimination of infected animals from a herd, and the discard of carcasses with suppurative lesions at slaughterhouses [103]. It has been reported that a number of factors can predispose to the development of these disorders, among other viral infections, that cause immunosuppression, for example with porcine reproductive and respiratory syndrome virus (PRRSV) [104].…”
Section: Pathogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle, T. pyogenes appears to be responsible for infections of the reproductive tract (5) and the mammary gland (6), as well as cases of pneumonia and liver abscessation of bovines and small ruminants (7). In swine, T. pyogenes is well known as a causative agent of different types of in ammation in various organs including the lung, heart, joints, mammary glands, and in the reproductive tract (8,9). Furthermore, T. pyogenes could be found in companion animals (4).…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, T. pyogenes appears to be responsible for infections of the reproductive tract [ 5 ] and the mammary gland [ 6 ], as well as cases of pneumonia and liver abscessation of large and small ruminants [ 7 ]. In swine, T. pyogenes is well known as a causative agent of different types of inflammation in various organs including the lung, heart, joints, mammary glands, and in the reproductive tract [ 8 , 9 ]. Furthermore, T. pyogenes could be found in companion animals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%